The Relationship Between Electronic Service Quality and Electronic Trust with Customer Loyalty in TikTok Shop Users Through Customer Satisfaction in Jabodetabek - Febriana, Ayu; Dita Puruwita; Nofriska Krissanya (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2024)
The purpose of this study was to determine the effect of electronic service quality, electronic trust, and customer satisfaction on customer loyalty of TikTok shop users in Jabodetabek. This quantitative research method collects data through questionnaires. A total of 250 respondents were sampled using purposive sampling techniques. The objects taken in this study were respondents who had used TikTok shop, aged 17-30 years, and domiciled in Jabodetabek. This study uses AMOS software version 24 and SEM (Structural Equation Model) to analyze and process research data. The results obtained in this study indicate that electronic service quality and electronic trust have a positive effect on customer satisfaction. In addition, electronic service quality and customer satisfaction have a positive effect on customer loyalty. Electronic service quality and electronic trust through customer satisfaction also have a positive effect on customer loyalty. However, electronic trust has no effect on customer loyalty.